2006
DOI: 10.1080/14634980600876039
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus geochemistry of recent sediments in the South Basin of Lake Winnipeg

Abstract: Lake Winnipeg supports the largest commercial fishery on Canadian Prairies. It has been influenced by a variety of environmental forces and anthropogenic activities. To gain a better understanding of recent changes in nutrient status of the lake, it is important to reconstruct its previous history from sedimentary records. Lacustrine sediments are known to be an important sink of many dissolved and suspended substances, including phosphorus, hence, they provide a permanent historical record of changes occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Both the temporal and spatial patterns of increasing growth rate could be the result of changes in nutrient inputs, exploitation, temperature (and hence, growing season), food web structure, or some combination of these factors, although it is not readily apparent why these factors might differentially affect these two species. The south basin of Lake Winnipeg generally receives more nutrientrich inflows than other regions of the lake (Brunskill et al, 1980), and sediment analyses have demonstrated a temporal increase in nutrient inputs in recent decades (Mayer et al, 2006). Higher nutrient inputs could provide a more productive food web for the percid community and may generate faster growth.…”
Section: Tablementioning
confidence: 97%
See 1 more Smart Citation
“…Both the temporal and spatial patterns of increasing growth rate could be the result of changes in nutrient inputs, exploitation, temperature (and hence, growing season), food web structure, or some combination of these factors, although it is not readily apparent why these factors might differentially affect these two species. The south basin of Lake Winnipeg generally receives more nutrientrich inflows than other regions of the lake (Brunskill et al, 1980), and sediment analyses have demonstrated a temporal increase in nutrient inputs in recent decades (Mayer et al, 2006). Higher nutrient inputs could provide a more productive food web for the percid community and may generate faster growth.…”
Section: Tablementioning
confidence: 97%
“…Minimum allowed mesh sizes have declined over time throughout Lake Winnipeg but have remained larger in the north basin where lake whitefish are the primary target and smaller in the channel and south basin where percids are the main target species. In addition to the effects of exploitation, the Lake Winnipeg fish community has experienced considerable environmental change through regulation of both inflowing tributaries and lake water levels (LWCNR, 1975), introductions of exotic species such as carp (Cyprinus carpio), white bass (Morone chrysops), and rainbow smelt (Osmerus mordax) (Stewart and Watkinson, 2004), and eutrophication from increased nutrient inputs (Mayer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The result has been a trend towards cultural eutrophication as evidenced by extensive algal blooms in recent years (LWSB, 2005). The Red River watershed system is the largest nitrogen and phosphorous source to Lake Winnipeg, contributing more of these nutrients than all other rivers that lead to it combined (Mayer et al, 2006;Patalas and Salki, 1992). Exploitation of Lake Winnipeg for hydroelectric purposes since the 1960s via control of the Nelson River outflow has hindered the lake's ability to discharge nutrients and other anthropogenic compounds during spring freshets, thereby increasing nutrient in-lake retention times and possibly accelerating the eutrophication process .…”
Section: Introductionmentioning
confidence: 99%
“…The period from the late 1980s to the early 2000s was characterized by very different types of change in these two ecosystems. In Lake Winnipeg, productivity was probably increasing in response to increasing nutrient inputs (Mayer et al, 2006), and the walleye population appears to have responded through increased abundance and growth and decreased age at maturity (Johnston et al, in press). In contrast, in eastern Lake Ontario a rapid increase in abundance of invasive dreissenid mussels in the early 1990s was followed by declines in both walleye and lake whitefish abundance (Hoyle et al, 2008).…”
Section: Discussionmentioning
confidence: 97%